2005
DOI: 10.2134/jeq2004.0414
|View full text |Cite
|
Sign up to set email alerts
|

Development of Bacteria and Benthic Total Maximum Daily Loads

Abstract: Two total maximum daily load (TMDL) studies were performed for Linville Creek in Rockingham County, Virginia, to address bacterial and benthic impairments. The TMDL program is an integrated watershed management approach required by the Clean Water Act. This paper describes the procedures used by the Center for TMDL and Watershed Studies at Virginia Tech to develop the Linville Creek TMDLs and discusses the key lessons learned from and the ramifications of the procedures used in these and other similar TMDL stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…The NRC (2008) estimates wetland construction for water storage to range from $100 to $3,000 per acre, while Randolph et al (2006) estimated stormwater and sediment controls added between $1,500 and $9,000 to the cost of new dwellings constructed in North Carolina. Stormwater also entrains Benham et al 2005) and cause economic loss from the closure of recreational areas (e.g., Rabinovici et al 2004). Houck (1999) estimated the costs for the development and implementation of TMDLs to be approximately $4 billion per state.…”
Section: Discussionmentioning
confidence: 99%
“…The NRC (2008) estimates wetland construction for water storage to range from $100 to $3,000 per acre, while Randolph et al (2006) estimated stormwater and sediment controls added between $1,500 and $9,000 to the cost of new dwellings constructed in North Carolina. Stormwater also entrains Benham et al 2005) and cause economic loss from the closure of recreational areas (e.g., Rabinovici et al 2004). Houck (1999) estimated the costs for the development and implementation of TMDLs to be approximately $4 billion per state.…”
Section: Discussionmentioning
confidence: 99%
“…The total WAT nonpoint source impact score of 1.02 x 10 17 for fecal coliforms under current conditions corresponds to a unit area load of 0.27 x 10 12 cells/acre/year for the 378,618 acre study area. Although WAT's results are at the upper end of the reported range for Milwaukee River watersheds, other studies, such as Benham et al (2005) show unit area loads as high as 1.9 x 10 12 cfu/acre/year for heavily agricultural areas. The possibility that WAT estimates of nonpoint source impacts are somewhat on the high side is consistent with Phase I WAT assumptions as the methodology does not incorporate loss processes such as die-off and losses during overland transport.…”
Section: Evaluation Of Resultsmentioning
confidence: 77%
“…The current version may be run for a single basin or aggregated basin; however, spatial flow routing is not yet available. Although GWLF has been widely used for hydrology and non-point source pollution (ShuKuang et al 2006;Benham et al 2005), a limited number of studies have been reported on the application of CANWET in Canada (Singh et al 2007;Boston et al 2006aBoston et al , 2006bWatts et al 2005). A flow chart that illustrates how the CANWET model works is presented in Fig.…”
Section: Fig 2 Location and Land Use Of Upper Canagagigue Creek Watmentioning
confidence: 99%